ANALISIS YURIDIS PENGGUNAAN BOM DALAM PENANGKAPAN IKAN DI WILAYAH PERAIRAN LAUT PULAU SEBUKU KABUPATEN LAMPUNG SELATAN (Studi Putusan Nomor : 321/Pid.Sus/2021/Pn.Tjk) - Cahya Ningrum, Bella; Siregig, I Ketut; Ramadan, Suta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2022)
The illegal act of fishing with explosives is currently regulated by Law No. 45 of 2009 on Fisheries, which states several legal provisions, including that waters are under the sovereignty and jurisdiction of the Unitary State of the Republic of Indonesia, as well as the Indonesian Exclusive Economic Zone, and are based on international provisions containing fish resources and potential fish farming land. In this work, a normative juridical approach and an empirical approach were used as research methods. Data is gathered through library research and field studies. The Defendant employed explosives in the shape of 6 (six) big bottles and 4 (four) tiny bottles obtained by purchasing 4 (four) kilograms of Ampo powder and then assembling them in a way that they could be used to bomb fish in order to carry out his action. The imposition of a crime in this case has the goal of not only punishing people who commit crimes, but also of fostering and educating people, so the judge believes that the sentence imposed on the defendant was appropriate and commensurate with his actions, based on aggravating and mitigating circumstances.